2022
DOI: 10.31235/osf.io/kv9bw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children left behind. New evidence on the (adverse) impact of grade retention on educational careers.

Abstract: This paper analyses the causal effect of grade retention on students’ high school track decisions in Italy. Using longitudinal administrative data, we propose a matching strategy to assess the impact of retention in institutional settings with substantial leeway in the promotion/retention decision. If decision makers differ in their propensity to retain students (strictness), it is reasonable to expect some of the students kept back to be fully on a par with others who are promoted. Assuming that strictness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…O problema da reprovação de estudantes na educação básica passou a ser sistematicamente registrado no Brasil a partir da criação do Inep, na década de 1930 (Gil, 2018), mas ganhou maior visibilidade como problema de política pública com a publicação do modelo Profluxo na década de 1990 (Fletcher, 1997;Ribeiro, 1991) No contexto de sistemas educacionais de fora do Brasil, vários autores propuseram tipologias de trajetórias escolares como forma de identificar redes de ensino, escolas e estudantes com desempenho insatisfatório ou maior risco de evasão (Manacorda, 2012;Langenkamp &;Carbonaro, 2018;Contini & Salza, 2022;Salza, 2022;Van Landeghem, 2022). Estas tipologias utilizam bancos de dados longitudinais para examinar a trajetória de estudantes em relação a eventos de fluxo escolar e em relação ao crescimento do desempenho acadêmico ao longo do tempo.…”
Section: Notas Sobre a Mensuração Da Permanência Escolarunclassified
“…O problema da reprovação de estudantes na educação básica passou a ser sistematicamente registrado no Brasil a partir da criação do Inep, na década de 1930 (Gil, 2018), mas ganhou maior visibilidade como problema de política pública com a publicação do modelo Profluxo na década de 1990 (Fletcher, 1997;Ribeiro, 1991) No contexto de sistemas educacionais de fora do Brasil, vários autores propuseram tipologias de trajetórias escolares como forma de identificar redes de ensino, escolas e estudantes com desempenho insatisfatório ou maior risco de evasão (Manacorda, 2012;Langenkamp &;Carbonaro, 2018;Contini & Salza, 2022;Salza, 2022;Van Landeghem, 2022). Estas tipologias utilizam bancos de dados longitudinais para examinar a trajetória de estudantes em relação a eventos de fluxo escolar e em relação ao crescimento do desempenho acadêmico ao longo do tempo.…”
Section: Notas Sobre a Mensuração Da Permanência Escolarunclassified
“…Traditionally, this measure has been seen as a necessary practice to provide more time for students who have difficulties in mastering the specific content of one year before moving on to the next. However, several studies have confirmed its ineffectiveness in improving the academic performance of affected students and even exacerbating educational inequality (Contini & Salza, 2022). Specifically, different studies show that being a repeater is identified as one of the main predictors of school failure (Arregi-Martínez et al, 2009;Ou & Reynolds, 2010).…”
Section: Introductionmentioning
confidence: 99%